Time diversity analysis based on predicted rain attenuation at KU, KA and V- bands using synthetic storm technique - Hassan, M. R.; Islam, Md. Rafiqul; Habaebi, Mohamed Hadi; Alam, Md Moktarul; Ahmad Zabidi, Suriza; Badron, Khairayu; Basahel, Ahmed (IEEE, 2021)
Satellite communication in the future is shifting to higher frequency Ka and V-bands. The fundamental issue in designing viable earth-to-satellite communication links at these bands is rain fade. In tropical areas, the problem is increased severely by the fact that high-intensity rainfall occurs for the majority of times in the year. One of the potential solutions presented by researchers to combat attenuation due to rain is the time diversity method. To explore the improvement, measured real-time rain attenuation data are necessary for time diversity analysis. However, the problem is that data in higher frequency bands such as the Ka and V bands are not available in most of the places. As a result, the Synthetic Storm Technique (SST) can be used to convert real-time rain rate data into real-time rain attenuation data at any required frequency. This research analyses data collected at IIUM's Kuala Lumpur campus over one-year period using one-minute integration time. Synthetic Storm Technique (SST) is used to estimate rain attenuation for Ku, Ka, and V-bands based on one-year recorded rain rate data. Time diversity gains are assessed and compared to available measured gain at Ku-band and that predicted by Matricciani's model using anticipated rain attenuation time series.